Six hours of hypoxia at 4500 m does not affect psychobiological parameters, regardless of glutamine supplementation: A randomized, double-masked, placebo-controlled clinical trial - Wanessa YG Souza; Valdir A Lemos; Marcus VL dos Santos Quaresma; Jean C Silvestre; Camila G Marques; Ronaldo V Thomatieli-Santos (Nutrition and Health, 2026)
Background: Hypoxia represents a challenge to human physiology and has been associated with the worsening of various brain functions. Glutamine mediates the synthesis of neurotransmitters such as glutamate and GABA. Aim: This study evaluated the effects of glutamine supplementation on mood and cognition in people under hypoxic conditions. Methods: It was a randomized, double-blind, placebo-controlled study in men aged 20 to 30 years. Participants were allocated into four groups: Normoxia placebo (NP), Normoxia glutamine (NG), Hypoxia placebo (HP), and Hypoxia glutamine (HG). The glutamine-supplemented groups received 20 g of glutamine daily for 6 days, followed by a 6-h hypoxia simulation at 13.5% O 2 in a normobaric chamber (the normoxic groups remained in the chamber with the device off). Pre- and post-hypoxia assessments encompassed physiological parameters (peripheral oxygen saturation, C-reactive protein, glutamine, heart rate, blood pressure) and psychobiological factors (mood profile, anxiety, memory, psychomotor performance). Summary: There is a significant decrease in peripheral oxygen saturation ( F (26, 3) = 17.1; p < 0.001; η 2 G = 0.527) and an increase in heart rate ( F (26, 3) = 6.05; p = 0.003; η 2 G = 0.167) due to hypoxia. However, psychobiological parameters remained unchanged by both hypoxia exposure and glutamine supplementation. In summary, prior glutamine supplementation did not produce statistically significant psychobiological effects under the present experimental conditions. However, subtle effects cannot be excluded due to sample size limitations.